Landscapes and landscape research in Germany - Marion Potschin; Olaf Bastian (Belgeo, 2004)
Landscape research has a long tradition in Germany. After Alexander von Humboldt introduced the term «landscape» 200 years ago, as the «total character of a region» (Totalcharakter von Erdgegenden), it became a key focus of study for Geography, stimulated by the work of Troll, Paffen, Schmithüsen, Neef and others. Although such ideas were, for a time, pushed into the background by wider reductionist views in science and Geography, it has recently remerged as an important research theme. In Germany Landscape Ecology has made a major contribution to contemporary Landscape Research, providing both scientific understanding and the basis of applications in fields such as Landscape Planning. Important methodological developments have included: landscape diagnosis, evaluation, the analysis and evaluation of landscape functions and the development of Leitbilder. Within Germany the current research agendas focuses on the relation between holism and the sectoral approach, principle of complementarity, relation of physical and perceptual approaches to the landscape concept, the problem of transformation, transdisciplinarity, scale-related issues. In the more applied arena, key issues are the study of environmental impacts/problems on landscapes in Germany arising out of intensive farming, industrialisation and urbanisation. A key task in Germany is to use the outputs from landscape studies to help protect the most valuable landscape and nature areas, as well as to develop strategies for the sustainable management of such areas alongside the more ordinary landscapes that are the home of most of our population.